2008
DOI: 10.1002/ana.21476
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase‐3β and tau genes interact in Alzheimer's disease

Abstract: Our genetic and biochemical analyses have identified a novel interaction between Tau and GSK-3beta in late-onset AD causative factors. Our data are consistent with an epistatic model of interaction where discordant levels of GSK3B and MAPT gene expression can lead to altered beta-catenin levels and pathogenicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 40 publications
(63 reference statements)
0
43
0
1
Order By: Relevance
“…Growing evidence indicate that GSK-3 is associated with risk for human primary neurodegenerative dementias, including AD and FTDP, via interaction with Tau (Kwok et al, 2008; Schaffer et al, 2008). In the present studies, Tau expression was associated with an increase in GSK-3, but no significant differences were observed in GSK-3 activation between Tau wt and Tau P301L , suggesting that both forms of Tau may induce GSK-3 activation, perhaps leading to increased Tau hyper-phosphorylation (Cho and Johnson, 2003, 2004).…”
Section: - Discussionmentioning
confidence: 99%
“…Growing evidence indicate that GSK-3 is associated with risk for human primary neurodegenerative dementias, including AD and FTDP, via interaction with Tau (Kwok et al, 2008; Schaffer et al, 2008). In the present studies, Tau expression was associated with an increase in GSK-3, but no significant differences were observed in GSK-3 activation between Tau wt and Tau P301L , suggesting that both forms of Tau may induce GSK-3 activation, perhaps leading to increased Tau hyper-phosphorylation (Cho and Johnson, 2003, 2004).…”
Section: - Discussionmentioning
confidence: 99%
“…The GSK3β rs6438552 allele that was associated with reduced GM volume in our previous study (Inkster et al, 2009) alters gene transcription in vitro, leading to hyperphosphorylation of its substrate, the microtubule-associated protein tau (encoded by the gene, Mapt) (Kwok et al, 2005(Kwok et al, , 2008. Serotonergic neuronal loss has been attributed to microtubuledependent mechanisms (Ren and Feng, 2007) and lithium treatment has been shown to reduce tau phosphorylation (Hong et al, 1997).…”
Section: Discussionmentioning
confidence: 94%
“…It was demonstrated that the MAPT gene rs242557 polymorphism that is part of the H1c subhaplotype, results in increased MAPT gene expression [34]. The authors also provided evidence that the H1/H2 MAPT haplotype interacts with functional SNPs in the GSK3B gene to affect the risk of Alzheimer's disease.…”
Section: Tau Protein (Microtubule-associated Protein Tau Mapt)mentioning
confidence: 97%